2016
DOI: 10.14814/phy2.12914
|View full text |Cite
|
Sign up to set email alerts
|

Saturated high-fat diet-induced obesity increases adenylate cyclase of myocardial β -adrenergic system and does not compromise cardiac function

Abstract: Obesity is a worldwide pandemic associated with high incidence of cardiovascular disease. The mechanisms by which the obesity leads cardiac dysfunction are not fully elucidated and few studies have evaluated the relationship between obesity and proteins involved in myocardial β‐adrenergic (βA) system. The purpose of this study was to evaluate the cardiac function and βA pathway components in myocardium of obese rats. Male Wistar rats were distributed into two groups: control (n = 17; standard diet) and obese (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 59 publications
5
22
1
1
Order By: Relevance
“…Our observation of reduced β‐adrenergic responsiveness in hearts of obese rats confirms previous findings, not only in isolated rat and rabbit hearts (Carroll et al., ; Carroll, Kyser, & Martin, ; Jiang et al., ; Lima‐Leopoldo et al., ), but also using cardiac membranes (Bass & Ritter, ; Chatelain et al., ; Strassheim et al., ), and more importantly, in vivo assessment in conscious conditions (Bunag et al., ; Bussey et al., ). In some studies, it was not possible to associate the reduced β‐adrenergic responsiveness of the obese heart with a downregulation of the β‐ARs (Carroll et al., ; Ernsberger, Koletsky, Baskin, & Foley, ; Ferron et al., ; Hohl et al., ; Minhas et al., ; Vileigas et al., ), potentially owing to differences in obese animal models and technical approaches. However, in several other studies, using obese Zucker rats, downregulation of β‐ARs was observed (Chatelain et al., ; Jiang et al., ; Strassheim et al., ), as found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observation of reduced β‐adrenergic responsiveness in hearts of obese rats confirms previous findings, not only in isolated rat and rabbit hearts (Carroll et al., ; Carroll, Kyser, & Martin, ; Jiang et al., ; Lima‐Leopoldo et al., ), but also using cardiac membranes (Bass & Ritter, ; Chatelain et al., ; Strassheim et al., ), and more importantly, in vivo assessment in conscious conditions (Bunag et al., ; Bussey et al., ). In some studies, it was not possible to associate the reduced β‐adrenergic responsiveness of the obese heart with a downregulation of the β‐ARs (Carroll et al., ; Ernsberger, Koletsky, Baskin, & Foley, ; Ferron et al., ; Hohl et al., ; Minhas et al., ; Vileigas et al., ), potentially owing to differences in obese animal models and technical approaches. However, in several other studies, using obese Zucker rats, downregulation of β‐ARs was observed (Chatelain et al., ; Jiang et al., ; Strassheim et al., ), as found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This, however, does not exclude the possibility that other β‐AR subtypes could be affected during obesity (Chatelain et al., ; Jiang et al., ; Strassheim et al., ) or play an important supportive role in the pathophysiology of obesity and diabetes (Cook et al., ; Li et al., ; Perez‐Schindler et al., ). More importantly, given that from a clinical viewpoint targeting β‐ARs with β‐blockers is commonly advised against in obese individuals owing to their unfavourable metabolic effects (Gress et al., ; Sharma et al., ) and given that β‐AR downregulation is most probably not the sole mechanism underlying the reduced β‐adrenergic responsiveness of the heart in obesity (Ferron et al., ; Vileigas et al., ), alternative mechanisms should be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this study, this type of carbohydrate was not used, since this would not allow knowing if the manifestation of the complications and comorbidities would be exclusively due to the increase of the amount of fat or its association with a carbohydrate with harmful capacity. It is believed that other factors may also have influenced this result as time of exposure to diet, fat percentage, and type (saturated or unsaturated) and source (animal or vegetable) of fatty acids and animal model [6,17,18,30,33,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size used in this study was based on the literature and on our previous studies. 13,[17][18][19] The control group was fed standard rat chow (RC Focus 1765, Agroceres ® , Rio Claro, SP, Brazil) containing 12.3% of kilocalories from fat, 57.9% from carbohydrates, and 29.8% from protein, whereas the obese group was fed one of four alternating high-fat diets (RC Focus 2413, 2414, 2415, and 2416, Agroceres ® , Rio Claro, SP, Brazil) containing 49.2% of kilocalories from fat, 28.9% from carbohydrates, and 21.9% from protein. The four high-fat diets had the same nutritional composition, except flavoring additives, namely, cheese, bacon, chocolate, or vanilla.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%